2016
DOI: 10.1136/bmjdrc-2016-000300
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care in rural youth with type 1 diabetes: a cross-sectional pilot assessment

Abstract: BackgroundType 1 diabetes mellitus (T1DM) presents a significant health burden for patients and families. The quality of care (QOC) among those living in rural communities is thought to be subpar compared with those in urban communities; however, little data exist to reflect this, especially in pediatric diabetes.ObjectiveThe purpose of this pilot study was to investigate diabetes QOC among families living in rural versus urban areas. 6 QOC markers were used to compare youth with T1DM: appointment adherence, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 47 publications
1
24
0
1
Order By: Relevance
“…10 A study by Stumetz et al revealed that participants from rural environments were less adherent to appointments and provider communication than participants from urban environments. 11 Ethnicity and socioeconomic indicators also demonstrate a role in compliance with screening, as one study showed the odds of screening for diabetic retinopathy being lower in black children and in those with poorer diabetes control. 12 Medical provider compliance in adhering to screening guidelines is essential to reduce the acute and chronic complications associated with T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…10 A study by Stumetz et al revealed that participants from rural environments were less adherent to appointments and provider communication than participants from urban environments. 11 Ethnicity and socioeconomic indicators also demonstrate a role in compliance with screening, as one study showed the odds of screening for diabetic retinopathy being lower in black children and in those with poorer diabetes control. 12 Medical provider compliance in adhering to screening guidelines is essential to reduce the acute and chronic complications associated with T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…Although our study population was uniformly well covered by medical insurance, more rural individuals than urban participants reported severe hyperglycaemia at diagnosis and use of herbal medicine, and their diabetes was less well controlled. Limited access to diabetes care, easy accessibility to traditional healers, lack of resources and frequent lack of stock of modern diabetes drugs have been reported to be the reasons for herbal medicine use and poor quality of diabetes care in LMICs [47,48]. There is a need to identify other barriers to quality diabetes care in the setting in which universal medical coverage is maximized and diabetes care decentralization to lower levels of the health system is established to improve equitable access to care.…”
Section: Discussionmentioning
confidence: 99%
“…where Type 1 and type 2 diabetes have been reported to be equally common [46] Although our study population was uniformly well covered by medical insurance, more rural individuals than urban participants reported severe hyperglycaemia at diagnosis and use of herbal medicine, and their diabetes was less well controlled. Limited access to diabetes care, easy accessibility to traditional healers, lack of resources and frequent lack of stock of modern diabetes drugs have been reported to be the reasons for herbal medicine use and poor quality of diabetes care in LMICs [47,48]. There is a need to identify other barriers to quality diabetes care in the setting in which universal medical coverage is maximized and diabetes care decentralization to lower levels of Further studies are required to assess risk factors for sub-types of diabetes and their aetio-pathology in rural and low-income settings and to identify effective interventions to inform guidelines to prevent and treat all forms of diabetes in LMICs.…”
Section: Clinical Characteristics Of the Participantsmentioning
confidence: 99%